2022
DOI: 10.5530/pres.14.4.65
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Some Naturally Occurring Monoterpenes viz d-Limonene, p-Cymene and Terpinolene on the Glycemic and Hepatic Function in a Rat Model of Type 2 Diabetes Mellitus

Abstract: INTRODUCTIONDiabetes mellitus is a group of metabolic disorders distinguished by a chronic hyperglycemic state exacerbated by defects in insulin secretion, insulin action, or both. Diabetes mellitus is classified into two types: i) Type 1 diabetes, also known as insulindependent diabetes mellitus (IDDM), is caused by a lack of insulin secretion by pancreatic beta cells. ii) Type 2 diabetes, also known as non-insulin dependent diabetes mellitus, is caused by a decrease in insulin sensitivity in target tissues. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…In the group treated with 12.5 mg/kg of the substance, the animals had a blood sugar level of 580 mg/dL, and after treatment, the value was reduced to approximately 290 mg/dL. A similar result was observed for the group treated with 25 mg/kg of the terpene; the value before treatment was approximately 500 mg/dL and after treatment, 200 mg/dL [98]. In in vitro research involving various types of terpenes commonly found in essential oils, such as myrcene, eugenol, eucalyptol, β-pinene, citrol and terpineol, the effect and potential benefits in the prevention and treatment of diabetes were evaluated based on the action of these compounds against the α-amylase enzyme (enzyme responsible for hydrolyzing oligosaccharides into monosaccharides, increasing blood sugar levels).…”
Section: -Phelandrenesupporting
confidence: 67%
“…In the group treated with 12.5 mg/kg of the substance, the animals had a blood sugar level of 580 mg/dL, and after treatment, the value was reduced to approximately 290 mg/dL. A similar result was observed for the group treated with 25 mg/kg of the terpene; the value before treatment was approximately 500 mg/dL and after treatment, 200 mg/dL [98]. In in vitro research involving various types of terpenes commonly found in essential oils, such as myrcene, eugenol, eucalyptol, β-pinene, citrol and terpineol, the effect and potential benefits in the prevention and treatment of diabetes were evaluated based on the action of these compounds against the α-amylase enzyme (enzyme responsible for hydrolyzing oligosaccharides into monosaccharides, increasing blood sugar levels).…”
Section: -Phelandrenesupporting
confidence: 67%
“…Monoterpenes can also have signifcant efects in diabetes by promoting hypoglycemic activity [24]. Studies have shown that monoterpenes include a wide variety of substances that possess antioxidant activity [25], which may prevent diabetic complications associated with oxidative stress [26,27]. Te general efects of monoterpenes on diabetes are schematized in Figure 1.…”
Section: Introductionmentioning
confidence: 99%